Instability of mechanical equilibrium in non-ideal gas mixtures - Fedorenko, O.V.; Poyarkov, I.V. (Recent Contributions to Physics, 2024)
To describe phenomena caused by the spatial heterogeneity of density, as well as the processes of natural gas purification, separation and enrichment of gas mixtures with certain components, it is necessary to take into account not only diffusion processes, but also convective currents that arise in the presence of a concentration gradient. Under certain conditions, in multicomponent gas mixtures, a violation of the stability of mechanical equilibrium is possible, i.e. a transition from a stable diffusion process to a convective one is realized in the systems under consideration. The use of linear stability analysis permits to determine on the plane of partial Rayleigh numbers the boundary of the transition of the diffusion process to convective, as well as the values of the thermophysical and geometric characteristics at which this transition is possible. When using this approach to describe experimental data obtained for gas systems containing components with pronounced non-ideal properties, discrepancies are observed. Therefore, the purpose of this work is to develop a method for determining the boundary of loss of stability of mechanical equilibrium in non-ideal gas mixtures. To achieve this goal, the mathematical model describing the change of regimes uses an equation of state in virial form. Based on the developed approach, stability maps were obtained for the C3H8 + CO2 – N2O and C3H8 + N2O – CO2 systems. A comparison of the calculation results with experimental data showed that the proposed technique could be used to determine the conditions for changing mixing modes in three-component gas mixtures containing components with real properties.